2016
DOI: 10.5114/aic.2016.61640
|View full text |Cite
|
Sign up to set email alerts
|

Conduction disturbances after transcatheter aortic valve implantation procedures – predictors and management

Abstract: Transcatheter aortic valve implantation (TAVI) has become a safe and efficient alternative to cardiac surgery in patients with severe aortic stenosis. In many countries the number of performed TAVI procedures equals the number of surgical implantations. Indications for TAVI are becoming more liberal, allowing a wider spectrum of patients to benefit from the advantages of transcatheter therapy. Due to its invasive nature, TAVI is associated with some complications such as conduction disturbances. Although these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Another meta-analysis found greater risk of major vascular complications and major and life-threatening bleeding in women [ 11 ]. Permanent pacemaker implantation and stroke rate were not significantly different between the groups in previously published data [ 9 , 12 , 22 ]. Nevertheless, some studies have also reported that women undergoing TAVI experience higher stroke rate in comparison with men [ 11 , 15 ].…”
Section: Discussionmentioning
confidence: 47%
“…Another meta-analysis found greater risk of major vascular complications and major and life-threatening bleeding in women [ 11 ]. Permanent pacemaker implantation and stroke rate were not significantly different between the groups in previously published data [ 9 , 12 , 22 ]. Nevertheless, some studies have also reported that women undergoing TAVI experience higher stroke rate in comparison with men [ 11 , 15 ].…”
Section: Discussionmentioning
confidence: 47%
“…The cause of this association is not clear but may be related to abnormal aortic and left ventricular outflow tract (LVOT) geometry resulting in increased radial forces being delivered to conductive tissue by the valve prosthesis. This observation is supported by procedural factors associated with new heart block, such as device implantation depth, angle of deployment, and prosthesis to LVOT diameter ratios …”
Section: Discussionmentioning
confidence: 79%
“…AV conduction damage could be due to hemorrhage, ischemia, or only inflammatory process. In the latter situation, there is a potential for AV conduction recovery . Hence, it is crucial to identify reliable parameters to predict the optimal profile of pacemaker use.…”
Section: Discussionmentioning
confidence: 99%